Alterations in the default mode network in rolandic epilepsy with mild spike-wave index in non-rapid eye movement sleep - Li, Yihan; Wang, Yingfan; Jiang, Ping; Sun, Jintao; Chen, Qiqi; Wang, Xiaoshan (Frontiers in Neuroscience, 2022)
Purpose: Rolandic epilepsy (RE) is one of the most common epilepsy syndromes during childhood. The aim of this study was to investigate the alterations in the default mode network (DMN) of RE patients whose spike-wave index (SWI) was within the 50-85% range during non-rapid eye movement (NREM) during sleep, as well as to detect early neuroimaging markers. Methods: Resting-state data was recorded for each subject using magnetoencephalography (MEG). DMN-related brain regions were chosen as regions of interest. The spectral power and functional connectivity (FC) of the DMN were estimated through the use of minimum norm estimation combined with Welch technique and corrected amplitude envelope correlation (AEC-c). Results: The patient group included 20 patients with NREM phase 50%≤ SWI <85% (mild SWI group), and 18 typical RE patients (SWI <50% group). At the regional level, the mild SWI group exhibited enhanced spectral power in the delta band of the bilateral posterial cingulate cortex and attenuated the spectral power in the alpha band of the bilateral posterial cingulate cortex. Enhanced spectral power in the bilateral precuneus in the delta band and attenuated spectral power in the right lateral temporal cortex in the alpha band were common across all RE patients. At the FC level, patients in the mild SWI group indicated increased AEC-c values between the bilateral posterial cingulate cortex in the delta band and between the left medial frontal cortex and bilateral posterial cingulate cortex in the alpha band. Increased AEC-c values between the right precuneus and left medial frontal cortex in the delta band, and between the left precuneus and right medial frontal cortex in the theta band, were common across all RE patients. Moreover, the spectral power in the bilateral posterial cingulate cortex in the alpha band and the AEC-c value between the bilateral posterial cingulate cortex in the delta band demonstrated good discrimination ability. Conclusions: The spectral power of the bilateral posterior cingulate cortex in the alpha band and the AEC-c value between the bilateral posterior cingulate cortex in the delta band may be promising indicators of early differentiation between mild SWI and typical RE.